Econometric Models of U.S. Energy Demand - Halvorsen, Robert (Lexington, Massachusetts: Lexington Books, D.C. Heath & Company, 1978)
This book presents the results of research on econometric models of demand for several major energy markets. Part 1 discusses long-run models of electricity demand in the residential, and industrial sectors. Part 2 discusses substitution among types of energy. Part 3 deals with the dynamic models of energy demand.
Includes index.
Bibliography: p. 161-166.
ne 18/04/2018
Loans
Keywords: Electric Utilities; Energy Policy